Klotho and PPAR Gamma Activation Mediate the Renoprotective Effect of Losartan in the 5/6 Nephrectomy Model - Maquigussa, Edgar; Paterno, Josne C.; de Oliveira Pokorny, Gabriel H.; da Silva Perez, Mariana; Varela, Vanessa A.; da Silva Novaes, Antônio; Schor, Nestor; Boim, Mirian A. (Frontiers in Physiology, 2018)
Renin angiotensin system (RAS) blockade reduces the progression of chronic kidney disease (CKD) independently of its antihypertensive effect. Ang II-induced fibrosis can be mediated by molecules such as klotho, PPAR- and the Wnt/-catenin pathway; however, the interaction among these molecules and RAS activation is not completely known. The aim of this study was to investigate a possible link between RAS, PPAR- and Klotho in the 5/6 nephrectomy (Nx) animals. Nx rats presented hypertension that was blunted by both losartan and propranolol; however, only losartan was able to reduce the expression levels of fibronectin FSP1 and TGF- in the remnant kidney. The anti-fibrotic Klotho and PPAR- were reduced in the remnant kidney, and losartan, but not propranolol, restored their levels. In contrast, the profibrotic Wnt 7a and Wnt 3 were upregulated and losartan prevented the increase in Wnts. In vitro, Ang II induced a decrease in both klotho and in PPAR- in MDCK cells, and this effect was blunted by losartan. However, klotho expression was increased by pioglitazone, an agonist of PPAR-, and suppressed by BADGE, an antagonist of PPAR-, suggesting that the effect of Ang II downregulating klotho is mediated by PPAR-. These data suggest that activation of the Wnt pathway together with downregulation of PPAR- that in turn suppresses klotho contribute to potentiating the profibrotic effect of Ang II.